Spiritualitas Misioner Paulus dan Kontekstualisasi Injili di Indonesia - Jonathan Octavianus; Juanda Juanda; Pieter G.O. Sunkudon (Sekolah Tinggi Theologia Nazarene Indonesia, 2026)
This article examines Paul’s missional spirituality in 1 Corinthians 9:19–23 as a theological foundation for Evangelical contextualization in Indonesia. The study aims to explore how Paul’s spirituality can provide a framework for contextual Christian witness within Indonesia’s pluralistic and culturally diverse society. Using a qualitative-theological approach through historical-grammatical and rhetorical analysis, this study argues that Paul’s statement of “becoming all things to all people” reflects a cruciform spirituality shaped by self-emptying and participation in the gospel rather than merely a missionary strategy. The findings show that Paul’s spirituality integrates fidelity to the gospel, contextual sensitivity, and missional engagement without compromising theological identity. This study concludes that authentic contextualization requires incarnational spiritual formation rather than superficial cultural adaptation. The article contributes theological implications for spiritual formation, theological education, discipleship, liturgical contextualization, and the church’s public engagement in Indonesia.